The relative contribution of mantle and continental crustal sources to primitive arc magmas: Insights from the early Palaeozoic Famatinian - Puna arc - Otamendi, Juan Enrique (2024)
Subduction zone magmatism plays a crucial role in driving the exchange of chemical elements between Earth´s interior and surface. This survey focuses on the compositional analysis of primitive mafic rocks within an ancient Early Palaeozoic subduction-related magmatic belt. The primary objective is to assess the petrological processes involved in the cycling of chemical elements from the Earth´s surface, through the slab and mantle reservoirs, to the crustal arc magmatic systems. By examining the composition of primitive mafic rocks and utilizing inverse modelling techniques, we estimate the composition of the ambient mantle source, which appears to have undergone depletion due to melt extraction before being metasomatized by slab agents. The inverse approach reveals that fluid-mobile elements (Th, U, La, Ce, and Sr) were primarily derived from the slab contribution and suggests that subduction had influenced the abundances of Nb and Ta in the modified mantle source. Conversely, Zr, Hf, and Ti were sourced from the ambient mantle. However, the available mineral/melt partition coefficients used in inverse modelling may overestimate the contribution of Sr and Nb from the slab. Instead, forward modelling is limited by the incomplete preservation of ancient volcanic arc geology. The forward mixing models that consider the interaction between slab-released sedimentary-derived melts and the ambient depleted mantle can explain the observed variations in Nd and Sr isotopic ratios in primitive mafic rocks. Two-component mixing shows that a small mass fraction (≤1.5 wt%) of average Cambrian continental sediments subducted beneath the Early Ordovician arc into a MORB-depleted mantle source account for the abundance of sedimentary-supplied elements such as Th, La, and Ba, as well as radiogenic isotope ratios of 143Nd/144N and 87Sr/86Sr in the primitive mafic magmas. The chemical and isotopic composition of deep-seated primitive mafic rocks reveals a decoupling between incompatible trace elements, which display minimal variation, and radiogenic isotopic ratios, which exhibit a wide range and reflect contributions from continental crustal reservoirs. To explain the observed variations in trace elements and isotopes, we propose a simple model involving simultaneous bulk assimilation (A) and imperfect fractional crystallization (IFC) in an open igneous system, where crystal accumulation and assimilation occur concurrently. Especially, deep crustal physicochemical interaction of primitive arc magmas with supracrustal host rocks may mask the expected clear signature of subarc mantle petrological processes. Our assessment of the Famatinian-Puna arc, an ancient subduction zone, concurs with estimates from active volcanic arcs, underscoring the general applicability of this study case to subduction zone magmatism.